The Effectiveness of Mindfulness-Based Intervention in Enhancing Self-Compassion among Older Adults - Nguyen Phuong Lan, Huynh Cong Du, (Opción, 2019)
Research has shown that there is a relationship between self-compassion and well-being among older adults, and that lack of self-compassion leads them to self-suffering, isolation and negative self-judgment, which affects their well-being. To address this, the current study attempts to determine whether the mindfulness-based intervention could enhance self-compassion among older adults. Results have revealed that participants in mindfulness training increased their level of self-compassion. The findings are significant for guidance counsellors, psychologists, social workers and older adults and caregivers